“Body Work”: Nurses and the Delegation of Medical Technology at the Ottawa Civic Hospital, 1947-1972 - Toman, Cynthia (Scientia Canadensis, 2006)
AbstractThe absence of ordinary women from histories of science and technology may be partially explained by what has been excluded as science, as well as who have been excluded as women of science. Although the delegation of medical technology to Ontario nurses increased rapidly during the mid-twentieth century, we know very little regarding how these ordinary women engaged in science and medical technology through the everyday practice of "body work." Gender structured the working relationships between predominantly-male physicians and predominantly-female nurses, shaping the process of delegation and generating significant changes in nurses' work as well as who provided bedside care. Trained nurses parlayed these new technological skills to their advantage, enabling the extension of technological care at the bedside and assuring their roles as essential for the functioning of the hospital system.